Effects of Low and Standard Intra-Abdominal Pressure on Postoperative Pain in Laparoscopic Cholecystectomy - Ali, Afaque; Hussain, Zaki; Jamal, Ayesha; Rahat, Fatima; Makshoof, Talha; Islam, Saqib (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyze the effects of low and standard intra-abdominal pressure on post-operative pain in laparoscopic cholecystectomy. Study Design: Comparative prospective study. Place and Duration of the Study: Department of General Surgery, Pak Emirates Military Hospital Rawalpindi, from Nov 2019 to Feb 2020. Methodology: The study comprised 53 patients who underwent Laparoscopic Cholecystectomy and were selected for the study. They were randomly divided into two groups by third-party randomization. The first group was operated on under low pneumatic pressure, i.e. 8-12 mmHg and the second group was operated on under high pneumatic pressure, i.e. (≥15 mmHg). The complaint of post-operative pain was evaluated using a visual analogue scale (VAS) in the next 12 hours. Results: The group that was operated under high pneumatic pressure showed a higher occurrence of post-operative pain (50.9%) than the group that operated under low pneumatic pressure. On the Visual Analogue Scale, 80.0% of patients with high pneumatic pressure showed a pain of score four or more which is very high compared to the other group (p <0.05). Conclusion: The patients operated for laparoscopic cholecystectomy under low-pressure pneumoperitoneum would suffer from less post-operative abdominal pain, which needs less analgesia and leads to early hospital discharge.